GROWTH RESPONSE OF RED DRAGON FRUIT (hylocereus costarincensis) STEM CUTTINGS TO PLANT GROWTH REGULATION (PGR) GROWTONE GIVING AND COMPOSITION OF CULTIVATING MEDIA - Heru Priyana; Elfin Efendi; Heru Gunawan (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted in Desa Tanjung Alam Dusun 1 Sei Dadap Sub-district, AsahanRegency, North Sumatera with flat topography with a height of ± 20 m above the see level, theresearch was conducted on March 03, 2018 - April 29, 2018.The materials used in this researchare PGR Growtone, seed, soil top, chicken manure, water, matador insecticide 25 EC (activematerial Lamda Sihalotrin), Dithane Fungicide M-45 (active material Mankozed). the tools used in this research are polybag, knife, bucket, hoe, ruler and plastic rope.This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is giving PGR Growtone with 3 levels ie: G0 = 0 g / l, G1 = 5 g / pl and G2 = 10 g / l. The second factor is giving the composition of cultivating media, with 4 levels ie M0 = 1: 0, M1 = 1: 1, and M1 = 1: 2 and M3 = 1: 3. The result of PGR Growtone study showed no significant effect on all observation parameters of dragon fruit stem cuttings. Giving of cultivating media composition showed significant effect on live cuttings percentage, the number of buds at the end of the experiment and budslength, with the best giving at M3 = 1: 3.The interaction between the application of PGR Growtone and the composition of cultivating media on the growth of red dragon fruit stem cuttings significantly affected to the live cuttings percentage, the number of buds at the end of the experiment and the bud length, with the best interaction of G2M3.